Iqbal and Malay World - EI-Muhammady, Muhammad ʿUthman (Intellectual Discourse, 2013)
‘Allāmah Dr. Muhammad Iqbal has attracted the attention of the Malay World as well as the Muslims in Southeast Asia. His prose works like The Reconstruction and his poetic compositions like Asrar-i-Khudi, Shikwah wa Jawab-i-Shikwah and others have been read and translated into Bahasa Melayu and Bahasa Indonesia. Most Indonesian and Malay front ranking leaders were influenced by his ideal of serving the cause of the Ummah. They used Iqbal's argument to mobilize the Muslims for reforms of their respective societies in particular in Malaysia and Indonesia.